Cattle wastewater as a low-cost supplement augmenting microalgal biomass under batch and fed-batch conditions. (15th February 2022) - Jain, Rahul; Mishra, Sanjeev; Mohanty, Kaustubha
Abstract: The utilization of costly chemical fertilizers and large freshwater requirements make the microalgae cultivation process uneconomical and highly unsustainable. To address this challenge, the present study aimed to integrate cattle wastewater (CW) (alternate for fertilizers) with domestic sewage wastewater (DSW) (substitute for freshwater) to cultivate Chlorella thermophile. To maximize the biomass yield, in-depth nutrient consumption patterns in both batch and fed-batch cultivation conditions were analyzed. Out of the eight (1%–4.5%) different CW feed concentrations tested during the batch cultivation, 2.5% CW set gave the highest biomass yield (2.17 g L −1 ), which was almost double the yield obtained using Bold Basal Medium (1.24 g L −1 ) and DSW without any CW addition (1.22 g L −1 ). However, the biomass yield declined with CW> 2.5%, and the ammonium (NH4 + ) inhibitory effect was observed. To address the (NH4 + ) toxicity challenge and further enhance the biomass yield, fed-batch experiments were designed with an intermittent CW feeding based on nutrient (NH4 + ) consumption pattern. The fed-batch cultivation resulted in twofold increased biomass yield (4.52 g L −1 ) in comparison to the batch process. The nutrient consumption pattern inferred that the (NH4 + ) concentration greater than 600 mg L −1 during the logarithmic phase was inhibitory for Chlorella thermophila cells. On biomass characterization, a significant improvement in protein content with CW addition was observed. The FAME analysis of the derived lipid stated its competitive biofuel quality with up-gradation of C:16 and C:18 groups. Based on the obtained results, projection analysis for an integrated rural model demonstrated the technology's potential for sustainable water management with valuable resource recovery. Graphical abstract: Image 1 Highlights: Eight CW concentrations were tested with DSW for C. thermophile growth. In batch mode, highest biomass yield (2.17 g L −1 ) was recorded using 2.5% CW addition. Fed-batch process resulted in further twofold increase in biomass yield (4.52 g L −1 ). Ammonium concentration >600 mg L −1 was found inhibitory to C. thermophila cells. Circular rural model suggested using developed approach shows technical feasibility.